Evolutionary Games in Economics - Friedman, Daniel (Econometrica, 1991)
Evolutionary games are introduced as models for repeated anonymous strategic interaction.The basic idea is that actions (or behaviors) which are more "fit," given the current distribution of behaviors, tend over time to displace less fit behaviors.Simple numerical examples motivate the key concepts of fitness function and compatible dynamics, and illustrate the relation to previous biological models.Cone fields are introduced to characterize the continuous-time dynamical processes compatible with a given fitness function.The analysis focuses on dynamic steady state equilibria and their relation to the static equilibria known as NE (Nash equilibrium) and ESS (evolutionary stable state).For large classes of dynamics it is shown that all stable dynamic steady states are NE and that all NE are dynamic steady states.The biologists' ESS condition is less closely related to the dynamic equilibria.The paper concludes with a brief survey of economic applications.